Clostridium butyricum RH2 Alleviates Chronic Foot Shock Stress-Induced Behavioral Deficits in Rats via PAI-1 - Zhang, Wenying; Ding, Tingyu; Zhang, Hong; Chen, Yuping; Liu, Liping; Jiang, Jinjin; Song, Siyuan; Cheng, Hao; Wu, Changhao; Sun, Jihu; Wu, Qin (Frontiers in Pharmacology, 2022)
Recent investigations have demonstrated that the chronic stress-induced behavioral disorders can be ameliorated by probiotics including Clostridium butyricum (C. butyricum) via the gut-brain-axis. However, the molecular mechanisms underlying the beneficial effects of C. butyricum on brain remain largely unknown. Here, we investigated whether chronic foot shock stress (CFSS) paradigm used for a hypertensive animal model could induce mood disorders such as anxiety, depression and cognitive impairments. Then, we assessed the impact of C. butyricum RH2 on the behavior disorders and neurobiological alterations in the hippocampus. Male Sprague-Dawley (SD) rats received intermittent electric shocks for consecutive 14 days and were treated with C. butyricum RH2 for 17 days. Anxiety- or depression-like behaviors were evaluated by open field test (OFT), and elevated plus maze (EPM) or tail suspension test (TST). The Morris water maze test (MWM) was used to evaluate the cognitive functions. CFSS intervention led to mild anxiety- or depression-like behavior or cognitive impairment and C. butyricum RH2 treatment reversed the CFSS-induced symptoms. The serum ACTH or CORT was increased following CFSS but was completely reversed by C. butyricum RH2 treatment. In the hippocampus of CFSS rats, the expressions of BDNF and TrkB were downregulated but proBDNF and P75NTR were upregulated. These expression changes were partially reversed by C. butyricum RH2, suggesting a mode of action on BDNF and proBDNF balance. CFSS exposure resulted in downregulation of tissue-type plasminogen activator (tPA) but upregulation of plasminogen activator inhibitor 1(PAI-1), which could contribute to the decrease in BDNF by reduced conversion from proBDNF to BDNF in the hippocampus. C. butyricum RH2 treatment reversed the upregulated PAI-1 but not the downregulated tPA, which was in parallel with the amelioration of behavioral abnormalities, suggesting a novel tPA independent mechanism for PAI-1 action. Our results demonstrate for the first time that C. butyricum RH2 attenuates stress-induced behavior disorders via inhibiting the expression of brain PAI-1.